PELAKSANAAN PEMBERIAN IJIN PEMERIKSAAN TERHADAP ANGGOTA DPRD KOTA SAMARINDA TERKAIT KASUS PIDANA KORUPSI DAN HAMBATANNYA - Mutiara Auliya Hadi (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACT                     There are several laws governing their must ask permission if you want to order an investigation into corruption cases committed by state officials. It is arranged in several different Act. Among other things contained in Article 220 of Law Number 27 Year 2009 on MPR, DPR, DPD and DPRD, in the aforementioned article required the written permission of the President or the Governor if you want to conduct an examination of the chairman, deputy chairman and members of the MPR, DPR, DPD and DPRD. But in reality, the performance of investigator corruption cases be hampered because of the inspection license. Must use the permission of the President regarding the examination of the affected members of the House of Representatives of corruption is one of the functions efforts to enforce checks and balances between the legislative and the executive. The purpose of this paper is to investigate the implementation of the licensing examination of Samarinda City Council member who exposed corruption cases. Knowing the obstacles in the licensing examination of Samarinda City Council member who exposed corruption cases.  Keywords : Corruption, Investigation and license